GOOD GOVERNANCE BASED PUBLIC SERVICES - Ronny Winarno; Endang Retnowati (NOTARIIL Jurnal Kenotariatan, 2019)
Public service as a reflection of service form to the public to complete the right and fundamental need and administrative service as it set in constitution of Republic Indonesia of 1945. State have an obligation to complete the right of every citizen through government system to increase quality and to guarantee public service in accordance with general principles of good governance. In fact, there are so many problems of public service, including incondidtence of public service. Therefore, this research is formulated into the roles and functions of public services in realizing good governance, the reform of the national legal system currently have the ability to transform the values of public services into the system of good governance based on the Constitution of the Republic of Indonesia 1945 and efforts to optimize public services that can achieve good governance. The analysis is carried out based on the rechtsstaats theory, stuffen theory and law enforcement theory that is adapted to the basis of ideology (rechtidee) and Indonesian constitution. The result is concluded that the role and function of public services is one reflection of Indonesia that guarantees legal certainty and protection of people's rights.The transformation of the values of public services is a product of the current national legal system reform which is intended as an effort to improve quality and ensure the provision of public services. Indeed, the realization of good governance must begin with the quality and validity of the implementation of public services.